Activation parameter changes as a mechanistic tool in SN2 reactions in solution - Vlasov, Vladislav Mikhailovich (European Journal of Chemistry, 2015)
Recent applications of activation parameters variation approach to the elucidation of SN2 reaction mechanisms have led to further clarifications of structures of transition states involved in the concerted reaction pathway. SN2 reactions in solution are reviewed with special emphasis of activation parameter variation ΔX≠ (X = H, S and G) with substituents in the nucleophile, leaving and nonleaving groups applying linear free energy relationships in order to evaluate the resultant δΔX≠ reaction constants. The use of internal enthalpy reaction constants δΔH≠int as a mechanistic tool is stressed when the structure of transition state in SN2 reaction is changed. Variations of the activation parameters in SN2 reactions and their mechanisms were analyzed.